(untitled) (Journal on Excellence in College Teaching, 2024)
Data from the 2010 administration of the Faculty Survey of Student Engagement were used to identify pairs of disciplines in which faculty want to be compared based on research practices, teaching practices, and perceptions of student engagement in academic activities. The goal of this study was to group disciplines by a method with which faculty agree, an approach that teaching and learning center staffs may use to structure faculty development programs and institutional researchers may use to present assessment data. Fifty-two disciplinary pairs were identified across the three categories. The implications of these findings are presented along with proposed directions for future research.